Diasporas and development - Merz, Barbara J. (ed.); Chen, Lincoln C (ed.); Geithner, Peter F (ed.) (Hyderabad, 2007)
Diasporas and Development aims to deepen the understanding of the promise and pitfalls of diaspora engagement and how it may help to bridge the distances between societies in an unequal world. Just as trade, finance, information and technologies are moving rapidly across borders, so too have labour markets and transnational migrant communities. Migrants are sending large quantities of money back to their countries of origin in the form of philanthropy, remittances and commercial investments. They are also sharing knowledge and skills learned or honed abroad. Is greater global equity an inevitable consequence of diaspora engagement in their countries of origin, or can it actually aggravate inequity? Diasporas and Development examines the positive$1 (Band sometimes negative$1 (Bimpacts of diaspora engagement through examination of policies and philanthropic modalities as well as specific regional examples of diaspora activity.s
Keywords: Migrant communities